Konstruksi Rumah Apung Sebagai Mitigasi Banjir Rob Di Bagan Deli Belawan Medan - Chelvin Prayuda Tarigan; Novalinda; Rahmadhani Fitri; Faurantia Forlana Sigit (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2023)
The surface around Belawan is nearly below the water level. So that at high tide Belawan automatically inundated. This is a phenomenon that has become a tradition at high tide. Tidal flood is a flood whose water comes from sea water. This tidal flood is a flood caused by the tide of sea water, until the tidal water inundates the land. This tidal flood is also known as inundation flood. This tidal flood will often hit or often occur in areas whose surface is lower than sea level. Because it is caused by the overflow of sea water that reaches the mainland, the water that is inundated due to this tidal flood has a color that tends to be clearer than the water in the usual floods. Tidal flood itself has several special characteristics or special characteristics it has. Some of the characteristics or characteristics of tidal flooding, among others, occur when the sea water is high, the color of the water is not too cloudy, it does not only occur when the rainy season arrives, usually occurs in areas that have a lower plains area than the ocean area. Impacts that arise due to tidal flooding, therefore many or small tidal floods must have a negative impact on the people who experience it, causing material losses, damaging buildings, causing the environment to become dirty and muddy, spreading germs. The floating house is a solution in tackling flooding due to high tide. By using a layout pattern with architectural design principles by considering drainage, comfort, and a clean and well-organized environment.